KAJIAN CULTURAL LAG DALAM KEHIDUPAN MASYARAKAT PERKAMPUNGAN BUDAYA BETAWI SETU BABAKAN PADA ERA GLOBALISASI - Nursyifa, Aulia (Prodi PPKn FKIP Universitas Pamulang, 2018)
This research aims to know the shape of cultural lag in the community of the Betawi Setu Babakan Village after the Ghetto culture of Engineering results the Government of DKI Jakarta. The method that used in this study is qualitative method. The research results showed that the Government of DKI Jakarta is trying to build a facility there are various means for protection of the Betawi in the era of globalization, but in practice local community contradictions occur less empowered, the community does not have the mental preparedness for menyeimbangi development that the more progressive so that experiencing a failed. Based on the theory of cultural lag of Ogburn, researchers sought to expose the failed, therefore needs to be an attempt to overcome the Cultural communities failed Betawi Setu Babakan by changing mindsets of society so that in accordance with the Master Plan of development of the Betawi Setu Babakan Village.